Cue theory - Arriaga, P.; Santos, A. C. (The international encyclopedia of media psychology, 2020)
There has been considerable debate about media effects, especially concerning the effect of exposure to violence on cognition, emotions, and aggressive behavior. Leonard Berkowitz systematically researched aggression and was an influential author who investigated the effects of this exposure in the 1960s. Berkowitz's contribution to the field of media exposure and the empirical evidence of his work are summarized and discussed in this entry. One of his early contributions was the “weapons-effect” hypothesis suggesting that aggression could be influenced by the presence of aggressive cues. He then developed the cognitive neoassociative model of affective aggression, which made important contributions to the discussion about the effects of exposure to violent movies, television, and video games. Several authors have replicated his studies and his theoretical model is still being used in research to address important societal problems.